Estimating the distance Estrada index - Yilun Shang (Kuwait Journal of Science)
Suppose $G$ is a simple graph on $n$ vertices. The $D$-eigenvalues$μ_1,μ_2,…,μ_n$ of $G$ are the eigenvalues of itsdistance matrix. The distance Estrada index of $G$ is defined as$DEE(G)=\sum_{i=1}^ne^{μ_i}$. In this paper, we establish newlower and upper bounds for $DEE(G)$ in terms of the Wiener index$W(G)$. We also compute the distance Estrada index for some concretegraphs including the buckminsterfullerene $C_{60}$.